Application of implicit scheme with AGE iterative method for solving fuzzy parabolic equation - Dahalan, A.A. (American Institute of Physics Inc., 2017)
The objective of this paper is to analyze the application of the Alternating Group Explicit (AGE) iterative method by using central finite approximation equation to solve linear system generated from the discretization of one-dimensional fuzzy diffusion problems. In addition, the formulation and implementation of the proposed method are also presented. The results obtained are then compared with Gauss-Seidel (GS) iterative method to illustrate their effectiveness and feasibility. © 2017 Author(s).